Construction Of Jogjakarta 90's Classic Car Fans Identity in The Perspective of Symbolic Convergence Theory - Aden, Zainul; Junaedi , Fajar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
A community is a social group of several organisms based on various environments. Jogjakarta 90's was formed based on the same interests and hobbies in loving the cars of the 1990s. This study focuses on knowing how the identity construction of a Jogjakarta 90's community is from the symbolic convergence theory's perspective. This study aims to determine the self-concept of Jogjakarta 90's classic car community members. Another aim of this research is to find out if the members of the Jogjakarta 90's classic car community construct their identities. This study used a qualitative descriptive method using interview and observation methods. Retrieval of informants in this study using purposive sampling. The results of this study show that in a Jogjakarta 90s community, there are no special rules for each member, and those who want to join Jogjakarta 90s can join immediately. In addition, the members of Jogjakarta 90 feel like members of and family because there is no age limit between them, making the members closer and maintaining good relations with each other. Furthermore, the symbolic convergence in Jogjakarta 90's resulted from equality between members with one. That equation formed through conversations about the '90s cars owned by members.